Characterization of Sixteenth to Nineteenth Century Ottoman Silk Brocades by Scanning Electron Microscopy-Energy Dispersive X-Ray Spectroscopy and High-Performance Liquid Chromatography - (:unkn) unknown (TAYLOR & FRANCIS INC, 2017)
Historical textiles in the Topkap Museum, which are called silk kaftans and brocades by art historians from the sixteenth and nineteenth were characterized by scanning electron microscopy-energy dispersive X-ray spectroscopy (SEM-EDX) and high-performance liquid chromatography with diode array detection for identification of metal threads and dyestuffs. In the most Ottoman textiles, metal threads, especially belonging to the sultans, were used as the gold gild. Although the chemical composition of the samples on the surface may easily be obtained by SEM-EDX, the thickness of the thin gold layer on metal threads cannot be obtained directly. Hence, the goal of this project is to describe whether metal threads are gilded or not and to measure coating thickness. A new method was developed for measuring the thickness of gold layer, and the modeling was reformed. The SEM-EDX results were interpreted in accordance with the theoretical models. The coating thickness of metal threads was subsequently measured in ancient textiles. The thickness, depth, and valuable metal composition in the threads of the artistic objects were obtained by this approach. Dye analysis was used to characterize the presence of indigotin, carminic acid, ellagic acid, and luteolin in the historical textiles.
Keywords: Dyes; high-performance liquid chromatography with diode array detection; metal thread; Ottoman silk brocade; scanning electron microscopy-energy dispersive X-ray spectroscopy; DIODE-ARRAY DETECTION; NATURAL DYES; IDENTIFICATION; HPLC; TEXTILES; THREADS; RED; METALS; INSECT; TURKEY